Some steady and unsteady heat conduction solutions in orthotropic circular cylinders. - Laura, P. A. A.; Sánchez Sarmiento, G.; Gutiérrez, R. H. (North Holland Publishing Co., 1979)
Fil: Laura, P. A. A. Comisión Nacional de Energía Atómica; Argentina